THE IMPACT OF RELIGIOSITY AS MODERATOR ON THE RELATIONSHIP BETWEEN ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION AND THE PERFORMANCE OF SMEs - Sefnedi Sefnedi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The purpose of this study was to examine the impact of religiosity as a moderator on the relationship between entrepreneurial orientation, market orientation, and the performance of small and medium-sized enterprises (SMEs). The population in this study was all managers or owners of SMEs in Padang city. The sampling technique used purposive sampling with 257 samples as a sample size. The findings displayed that entrepreneurial orientation and market orientation had a positive and significant effect on the performance of SMEs. Religiosity did not affect the performance of SMEs. However, it strengthened the relationship between entrepreneurial orientation, market orientation, and the performance of SMEs.